2020
DOI: 10.22541/au.160363803.32074105/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic balancing selection is key to the invasive success of the fall armyworm

Abstract: A successful biological invasion involves survival in a newly occupied environment. If a population bottleneck occurs during an invasion, the resulting depletion of genetic variants could cause increased inbreeding depression and decreased adaptive potential, which may result in a fitness reduction. How invasive populations survive in the newly occupied environment despite reduced heterozygosity and how, in many cases, they maintain moderate levels of heterozygosity are still contentious issues 1. The Fall arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…One would be the uncharacteristic similarity between the ancestral population for all the invaded regions, which is indicative of a recent and a common source. Secondly, most of the earlier studies on FAW sequences in India have reported low levels of genetic variation, similar to the one found in Africa and East Asia [7,18,[21][22]. Thirdly, the distribution of the novel haplotypes in Indian populations is unimodal, typical of founder effect with recent population expansion.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…One would be the uncharacteristic similarity between the ancestral population for all the invaded regions, which is indicative of a recent and a common source. Secondly, most of the earlier studies on FAW sequences in India have reported low levels of genetic variation, similar to the one found in Africa and East Asia [7,18,[21][22]. Thirdly, the distribution of the novel haplotypes in Indian populations is unimodal, typical of founder effect with recent population expansion.…”
Section: Discussionsupporting
confidence: 51%
“…In general, Tpi gene was found to accurately predict the host association in invasive populations [3,[18][19]. The discordance between the two markers was re ective of the hybrid nature of the invasive populations which was subsequently corroborated with whole genome studies [20][21]. Barring the detection of two maternal COI lineages and a limited number of Tpi haplotypes, genetic variability in the invasive populations was found to be very low.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations